Advancements in Rotor Dynamics: Balancing Techniques and Vibration Reduction - Priya Mehta (Journal of Advanced Research in Mechanical Engineering and Technology, 2025)
Rotor dynamics plays a critical role in the efficiency, reliability, and operational safety of rotating machinery used in aerospace, automotive, power generation, and industrial applications. The study of rotor dynamics focuses on understanding the vibrational behavior, stability, and balancing of rotating components to ensure smooth operation and prevent mechanical failures. Unbalanced rotors and excessive vibrations can lead to structural damage, increased energy consumption, premature wear of machine components, and costly maintenance or downtime. As industries demand higher rotational speeds, improved energy efficiency, and extended operational life, advancements in rotor dynamics have become increasingly significant. This review explores recent developments in balancing techniques and vibration reduction strategies to enhance rotor performance. Traditional static and dynamic balancing methods are discussed alongside cutting-edge approaches such as finite element analysis (FEA), computational fluid dynamics (CFD), and machine learning-based fault prediction models. Additionally, emerging technologies in active and passive vibration control, including smart materials, piezoelectric actuators, tuned mass dampers (TMDs), magnetic bearings, and adaptive balancing mechanisms, are examined for their potential in mitigating rotor instability. Furthermore, the article highlights the role of artificial intelligence (AI) and the Internet of Things (IoT) in predictive maintenance, enabling real-time condition monitoring and early fault detection in high-speed rotating systems. The integration of digital twin technology is also explored, providing insights into virtual simulation-based rotor diagnostics and performance optimization. As industries move toward more sustainable and high-performance rotating machinery, future research must focus on self-balancing rotor systems, AI-assisted optimization, advanced material coatings, and hybrid vibration control solutions. The combination of experimental studies, computational modeling, and real-time adaptive control systems will be key to advancing rotor dynamics, ensuring higher efficiency, reduced downtime, and enhanced reliability in critical engineering applications.